Extended Spectrum Beta Lactamases (ESBL) producing Salmonella Isolated from Raw Goat Meat and Water from Slaughterhouses in Chitwan, Nepal - Pudasaini, Bibek; Thapa, Parisha; Chaudhary, Amar Nath; Sharma, Supriya (Nepalese Journal of Agricultural Sciences, 2026)
Salmonella contamination in raw meat and water used in slaughterhouses poses a significant health risk, particularly with strains producing Extended Spectrum Beta Lactamases (ESBL). This study aims to determine the prevalence of Salmonella and its ESBL activity in raw goat meat and water used in slaughterhouses, examining risk factors associated with contamination. In this cross-sectional study conducted between November 2022 and January 2023, a total of 50 raw goat meat and 50 water samples were collected from slaughterhouses in Bharatpur Metropolitan city, Nepal. Microbiological and biochemical techniques were used to identify Salmonella isolates, and ESBL production was confirmed by combined disc test. Risk factors, including slaughterhouse type, water quality, and cleaning practices, were analyzed using chi square tests. Salmonella was isolated from 8% of meat and 44% of water samples. Among Salmonella-positive samples, ESBL activity was observed in 50% of meat and 40.9% of water samples. Significant associations were found between Salmonella presence and risk factors such as open slaughterhouse type, direct cash transactions, use of non-potable water, and lack of regular cleaning (p < 0.05 for each).The findings underscore the need for improved sanitation, regular cleaning, and water quality management in slaughterhouses. Implementing these measures and enhancing public awareness can mitigate Salmonella contamination risks and reduce the spread of antimicrobial resistance. Regulatory oversight and best practice guidelines should be developed and enforced in Nepal’s slaughterhouses to protect public health and address growing antimicrobial resistance challenges